Analysis of Factors Influencing the Choice of Non-Hormonal Long-Acting Contraceptive Methods - Emi Juniarita Br. Barus; Karnirius Harefa; Ika Nursaputri (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The Maternal Mortality Ratio (MMR) in Indonesia is still relatively high, with one of the causes being unintended pregnancies. One way to reduce MMR is by increasing the use of long-acting non-hormonal contraceptives (LA/NGCs), such as IUDs and MOWs. Factors influencing the selection of non-hormonal LA/NGCs include attitude, trust, location/distance, spousal support, and healthcare facilities. Objective: This study aims to analyze the factors influencing the selection of non-hormonal long-acting contraceptives (LA/NGCs) in Tanjung Balai District, Asahan Regency, focusing on attitude, trust, location/distance, and the role of healthcare workers. Methods: This study used a quantitative design with a cross-sectional approach. Data were collected through questionnaires distributed to 92 respondents, who were couples of reproductive age (PUS). The variables analyzed include attitude, trust, location/distance, spousal support, and healthcare facility services. The statistical test used was chi-square to examine the relationship between independent and dependent variables (the selection of non-hormonal LA/NGCs). Results: The results showed a significant relationship between attitude, trust, location/distance, and the role of healthcare workers with the selection of non-hormonal LA/NGCs (p < 0.05). Respondents with a positive attitude, trust in healthcare providers, easy access to healthcare facilities, and quality services were more likely to choose non-hormonal LA/NGCs. Conclusion: This study concludes that factors such as attitude, trust, location/distance, and the role of healthcare workers significantly influence the selection of non-hormonal long-acting contraceptives. Therefore, increasing knowledge and improving access to healthcare services is crucial to encourage the selection of these contraceptive methods